2006
DOI: 10.1177/1363459306064477
|View full text |Cite
|
Sign up to set email alerts
|

Who serves the underserved? Predictors of physician care to medically indigent patients

Abstract: Using a national sample of 466 doctors, this work is the first to determine how sociodemographic characteristics, family lives, educational experiences and work environments combine over the life course to shape physician attitudes and behaviors toward serving the medically indigent. Survey data reveal that most physicians have positive experiences with indigent patients, and feel responsible for providing care for the needy. On average, one-quarter of doctors' patients are medically indigent, and physicians p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…38 Likewise, Chirayath found an overall association between practicing physicians' attitudes towards underserved populations and caring for the underserved. 39 To explain these associations, existing theoretical frameworks have identified that factors associated with physicians' service to underserved patients may include practice setting, favorable changes in income, emotional connections to underserved populations, and commitments to underserved populations throughout the life course. [39][40][41][42] Our findings add to the existing literature by showing the new finding of associations between attitudes and caring for underserved patients among resident physicians, and indicate that residents who express an interest in topics relevant to underserved patients may be more likely to provide volunteer service.…”
Section: Discussionmentioning
confidence: 99%
“…38 Likewise, Chirayath found an overall association between practicing physicians' attitudes towards underserved populations and caring for the underserved. 39 To explain these associations, existing theoretical frameworks have identified that factors associated with physicians' service to underserved patients may include practice setting, favorable changes in income, emotional connections to underserved populations, and commitments to underserved populations throughout the life course. [39][40][41][42] Our findings add to the existing literature by showing the new finding of associations between attitudes and caring for underserved patients among resident physicians, and indicate that residents who express an interest in topics relevant to underserved patients may be more likely to provide volunteer service.…”
Section: Discussionmentioning
confidence: 99%
“…(20)(21)(22)(23)(24) Similarly, students who grow up in urban underserved areas are more likely to practice in inner cities. (20) Under-represented minority physicians (25;26) and women (26) are more likely to care for underserved populations. Personal values, spirituality, and mentoring also increase students' likelihood of choosing service careers.…”
Section: What We Know About Factors Affecting Medical Student and Residmentioning
confidence: 99%
“…Personal values, spirituality, and mentoring also increase students' likelihood of choosing service careers. (25)(26)(27) Finally, longitudinal, comprehensive medical school and residency educational programs with the explicit goals of preparation of students and physicians for underserved practice have demonstrated clear success. (28)(29)(30)(31)(32)(33) Despite the importance of these issues, and the understanding gained from previous researchers, significant gaps in knowledge remain about the role of medical student debt, scholarship and loan programs, type of school, curriculum, institutional culture, and potential income on medical students' specialty choices and decisions to care for underserved populations.…”
Section: What We Know About Factors Affecting Medical Student and Residmentioning
confidence: 99%
“…While some quantitative research shows that physicians’ attitudes toward the medically indigent (who are disproportionately minority) are influenced by circumstantial and social factors such as relationships with mentors (Chirayath 2006), a variety of programs with different strengths and limitations have been developed to inculcate health care providers with new information and attitudes toward diverse groups. The enterprising cultural competence coordinator or health care provider can quickly locate myriad curricula, tools, videos, bibliographies, vignettes, and other resources online.…”
Section: Technologies Of Culturally Appropriate Health Carementioning
confidence: 99%